Modelling of interfacial transition zone effect on resistance to crack propagation in fine-grained cement-based composites (Fracture and Structural Integrity, 2017)
In this paper, the attention is paid to investigation of the importance of the interfacial transition zone (ITZ) in selected fine-grained cement-based composites for the global fracture behaviour. This is a region of cement paste around the aggregate particles which specific features could have significant impact on the final behaviour of cement composites with a crack tip nearby this interface under applied tension. The aim of this work is to show the basic interface microstructure by scanning electron microscopy (SEM) done by MIRA3 TESCAN and to analyse the behaviour of such composite by numerical modelling. Numerical studies assume two different ITZ thicknesses taken from SEM analysis. A simplified cracked geometry (consisting of three phases – matrix, ITZ, and aggregate) is modelled by means of the finite element method with a crack terminating at the matrix–ITZ interface. ITZ’s modulus of elasticity is taken from generalized self-consistent scheme. A few conclusions are discussed based on comparison of the average values of the opening stress ahead of the crack tip with their critical values. The analyses dealing with the effect of ITZ’s properties on the stress distribution should contribute to better description of toughening mechanisms in silicate-based composites.
Keywords: Fine-grained concrete; Interfacial transition zone; Scanning electron microscopy; Three-point bending fracture test; Effective fracture toughness